Evaluation of a DNA probe for the quantitative detection of common bacterial blight in common bean and its application in a breeding program - Constable, EC; Michaelis, TE; Goodwin, PH; Mayer, Jorge Edgard; Pastor Corrales, Marcial A. (Springer, 1996)
Breeding of Phaseolus vulgaris L. for resistance to common bacterial blight (CBB) can be done with visual evaluations of symptoms to distinguish broad resistance classes, but a more quantitative measure was needed for genetic studies of resistance. A novel method of evaluation was developed by quantifying Xanthomonas campestris pv. phaseoli (XCP) in bean leaf tissue infected with CBB using a 32P-labeled probe and densitometric analysis of hybridization signals. Quantification of bacterial populations using the probe was highly correlated (r=0.98) with the number of colony forming units (CFU) from plate counts of the same leaf samples. The probe was used to follow XCP population dynamics on susceptible (BAT 41) and resistant (OAC 88-1) bean genotypes. OAC 88-1 supported a maximum XCP population which was approximately tenfold less than BAT 41. The probe was also used to study an F2/F3 population segregating for resistance. Narrow sense heritability estimates were less for resistance measured on the basis of bacterial populations (0.18–0.26) than on visual scores of symptoms (0.29–0.38). The anticipated response to selection for CBB resistance would be less based on bacterial numbers than based on symptom expression in this population. In breeding for resistance to CBB, selection based on visual symptoms combined with measurements of XCP populations using a DNA probe can be used to develop bean genotypes that are both resistant to symptom development and bacterial multiplication.